Respuesta :

Answer:

3x^2-x-6

Step-by-step explanation:

f(x) = 3x^2 - 4

g(x) = x+2

(f - g)(x)= 3x^2 - 4-( x+2)

Distribute the minus sign

(f - g)(x)= 3x^2 - 4- x-2

Combine like terms

            = 3x^2-x-6

Answer:

(f - g)(x) = 3 x² - x - 6

Step-by-step explanation:

Given :-

  • f(x) = 3x² - 4
  • g(x) = x+2

Find :-

  • (f - g)(x).

Solution :-

(f - g)(x) = 3 x² - 4 - ( x + 2 )

Distribute the ( - ) minus sign

(f - g)(x) = 3 x ² - 4 - x - 2

Combine like terms

(f - g)(x) = 3 x ² - x - 4 - 2

(f - g)(x) = 3 x² - x - 6